2017
DOI: 10.3892/or.2017.5383
|View full text |Cite
|
Sign up to set email alerts
|

Role of miR-647 in human gastric cancer suppression

Abstract: MicroRNAs (miRNAs) regulate various oncogenes concomitantly, resulting in tumor suppression. They regulate proliferation and migration pathways in tumor development, suggesting a potential therapeutic role. In the present study, we found that miR-647 was markedly downregulated in gastric cancer (GC), and was significantly correlated with reduced tumor size and metastasis. In addition, miR-647 was also reduced in GC cell lines. Furthermore, overexpression of miR-647 in the GC cell lines inhibited cell prolifera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 40 publications
(39 reference statements)
1
30
0
1
Order By: Relevance
“…Moreover, we found that the cell invasion ability of glioma cells was suppressed by miR‐647 mimic. In summary, the results of the present study indicated that miR‐647 may function as a tumor suppressive role in glioma, which is consistent with its role in non‐small cell lung cancer or gastric cancer . A recent study reported that miR‐647 expression can be regulated by long non‐coding RNA PROX1‐AS1 and regulates gastric cancer progression and aggressiveness .…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Moreover, we found that the cell invasion ability of glioma cells was suppressed by miR‐647 mimic. In summary, the results of the present study indicated that miR‐647 may function as a tumor suppressive role in glioma, which is consistent with its role in non‐small cell lung cancer or gastric cancer . A recent study reported that miR‐647 expression can be regulated by long non‐coding RNA PROX1‐AS1 and regulates gastric cancer progression and aggressiveness .…”
Section: Discussionsupporting
confidence: 88%
“…In summary, the results of the present study indicated that miR-647 may function as a tumor suppressive role in glioma, which is consistent with its role in non-small cell lung cancer or gastric cancer. 7,8 A recent study reported that miR-647 expression can be regulated by long non-coding RNA PROX1-AS1 and regulates gastric cancer progression and aggressiveness. 13 A limitation of the present study is that we did not explore the upstream regulator of miR-647 in glioma and hence further investigations are needed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…79 MiR-647 has two expression patterns in GC tissues and cell line, so that downregulation of this miRNA in GC tissues significantly associated with reduced metastasis and tumor size 80 also, overexpression of miR-647 inhibited cell proliferation, promoted cell cycle arrest and apoptosis of GC cell lines, and appreciably suppressed tumor growth in vivo. 80 Countless miRNAs also act as biological prognostic biomarkers for consequence of GC patients. Li et al reported that the high-risk miRNAs (miRNA-10b, miRNA-21, miRNA-223, and miRNA-338) signature was independent predictors of poor prognosis in GC.…”
Section: Mirnas As Diagnostic and Prognostic Biomarkers In Gcmentioning
confidence: 99%